1993
DOI: 10.1093/oxfordjournals.humrep.a137986
|View full text |Cite
|
Sign up to set email alerts
|

Infertility: Oocyte donation: comparison between recipients from different age groups

Abstract: Oocyte donation was carried out in 87 patients in 141 replacement cycles. These patients received oocytes from 108 women undergoing assisted reproductive technology procedures at our centre. Standardized hormonal replacement therapy and in-vitro fertilization procedures were performed. We divided recipients into four groups according to their age (group A, 21-35 years; B, 36-40 years; C, 41-49 years; and D, 50-61 years). Oocytes donors were 21-35 years old, and equally spread across these different age groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 0 publications
0
24
0
2
Order By: Relevance
“…Several studies have addressed the effect of wom an's age on the success of IVF treatm ent with do nated oocytes (e.g., Sauer et a l [12,16], Abdalla et al [13], Flamigni et al [19]; Navot et al [14]; Check et al, [15]; Cano et al [21]; Borini et al [20]). The results were contradictory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have addressed the effect of wom an's age on the success of IVF treatm ent with do nated oocytes (e.g., Sauer et a l [12,16], Abdalla et al [13], Flamigni et al [19]; Navot et al [14]; Check et al, [15]; Cano et al [21]; Borini et al [20]). The results were contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was corroborated by Check et al (15), who could not find an aging effect of the uterus when hormone supplementation was prolonged until the endometrium thickness was >10 mm. However, this factor cannot explain the aging effects of the uterus found by Flamigni et al (19), Cano et al (21), and Borini et al (20), whose patients were all supplemented with high doses of P. More over, Meldrum (22) suggested that the low rate of spontaneous abortions observed in older women after donor IVF could be explained by the corrective effect of the hormone replacement. However, Cano et al (21) used high doses of P and found an in creased rate of spontaneous abortion in women of >40 years.…”
mentioning
confidence: 94%
“…Egg sharing has been reported in Australia [12], Belgium [13][14][15], Canada [16], Greece [12], Spain [12], the UK [12,[17][18][19][20][21][22][23][24][25][26]103,104] and the USA [27][28][29][30][31][32][33][34][35][36][37], and was practiced in Italy until legislation passed in 2004 that prohibited all forms of donor and third-partyassisted-conception procedures [38][39]. It is the sole legally permissible form of egg donation in Denmark [3,105] and Israel [40].…”
Section: Egg Sharingmentioning
confidence: 99%
“…Several reports provide no information regarding outcomes for donors at all [29,[32][33][34]37]. Others, while providing outcome data for both donors and recipients, are restricted to pregnancy -or to pregnancy and implantation outcomes only -and provide no information regarding live births [19,28,30,31,35,36,38]. Only five studies provide data regarding live-birth outcomes for donors [14,17,25,26,34].…”
Section: Concerns Regarding Egg Sharingmentioning
confidence: 99%
See 1 more Smart Citation